PERANAN SISTEM KEARSIPAN DALAM PENATAAN ADMINSTRASI DATA PASIEN DI RUMAH BAGIAN REKAM MEDIK RUMAH SAKIT UMUM DAERAH TOTO KABILA KABUPATEN BONE BOLANGO TAHUN 2011 - Sri Hantuti Paaramata (Universitas Muhammadiyah Gorontalo, 2019)
This research aims to To get an idea of Filing performed by Toto Kabila's Hospital at the Medical Record that includes storage, transfer and destruction, as well as determine the factors that support and hinder data management and archiving at the Hospital Medical Records Toto Kabila. The method this research is a qualitative descriptive study, the method used in this study by drawing a random sample, the techniques of data collection through interviews, observation field / direct observation and documentation. Based on these results, Toto Hospital Medical Records Personnel Kabila for archiving disciplines is still very low, support for archiving facility is lacking as well as lack of education and training for hospital employees Toto Kabila Medical Records the Conclusions is the issues that dominate in the implementation of Medical Records Hospital Toto Kabila is limited employees who understand the field of archiving, so it is necessary the hospital Toto Kabila to provide education and training to existing employees currently in the field of Medical Records. Keywords: Filing Systems, Medical Records, Patient Data Administration, Inpatient and Outpatient